2015
DOI: 10.1186/s13045-015-0189-2
|View full text |Cite
|
Sign up to set email alerts
|

T cells are functionally not impaired in AML: increased PD-1 expression is only seen at time of relapse and correlates with a shift towards the memory T cell compartment

Abstract: BackgroundT cell function is crucial for the success of several novel immunotherapeutic strategies for the treatment of acute myeloid leukemia (AML). However, changes in phenotype and function of T cells have been described in various hematologic malignancies, mimicking T cell exhaustion known from chronic viral infections. Detailed knowledge about phenotype and function of T cells in AML patients at different stages of the disease is indispensable for optimal development and application of immunotherapeutic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
122
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(132 citation statements)
references
References 60 publications
8
122
0
2
Order By: Relevance
“…26 In addition, patients at diagnosis show similar expression profiles of inhibitory molecules (PD-1, 2B4, TIM-3, Lag-3, and CD160) compared with healthy donors, thus lack of T-cell responsiveness as a result of negative immune checkpoint molecules is less likely. 27,28 Furthermore, the proliferative capacity of residual T cells in chemotherapy-induced cytopenic AML patients was preserved and higher than that observed in ALL. 29 Finally, in relapsed patients after allogeneic stem cell transplantation, both PD-1 and 2B4 expression on T cells was higher and associated with a shift toward a differentiated T-effector memory phenotype.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…26 In addition, patients at diagnosis show similar expression profiles of inhibitory molecules (PD-1, 2B4, TIM-3, Lag-3, and CD160) compared with healthy donors, thus lack of T-cell responsiveness as a result of negative immune checkpoint molecules is less likely. 27,28 Furthermore, the proliferative capacity of residual T cells in chemotherapy-induced cytopenic AML patients was preserved and higher than that observed in ALL. 29 Finally, in relapsed patients after allogeneic stem cell transplantation, both PD-1 and 2B4 expression on T cells was higher and associated with a shift toward a differentiated T-effector memory phenotype.…”
Section: Discussionmentioning
confidence: 94%
“…29 Finally, in relapsed patients after allogeneic stem cell transplantation, both PD-1 and 2B4 expression on T cells was higher and associated with a shift toward a differentiated T-effector memory phenotype. 28 Overall, these observations suggest that intervention with a T cell redirecting therapeutic at early diagnosis or in combination with chemotherapy is a rational approach.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory pathways, including programmed cell death protein 1 (PD-1), T-cell immunoglobulin domain, and mucin domain 3 (TIM-3), 2B4, CD160, B-and T-lymphocyte attenuator (BTLA), and lymphocyte-activation gene 3 (LAG-3), contribute to the development of T-cell exhaustion (14)(15)(16)(17)(18)(19)(20). Several studies, including ours, have demonstrated an involvement of inhibitory pathways in AML progression (21)(22)(23)(24)(25). Strategies for blocking immune suppression are attractive due to their relatively simple administration and the resulting increased T-cell activity and enhanced tumor killing.…”
Section: Introductionmentioning
confidence: 80%
“…These regulations could be the result of chronic stimulation leading to enhanced T cell exhaustion. The CMV status of the patients might play a role here, however, recent papers showed defects in T cell function irrespective of CMV serostatus [48, 49]. …”
Section: Discussionmentioning
confidence: 99%